Collaborative information system: connecting the government, university, and industry - Hasan, Muhammad Rabiul; Moses, Golooba; Maulid, Swaleh; Ahmad Dahlan, Abdul Rahman (International Business Information Management Association, 2011)
The study explores the concept of collaborative information system among three main partners such as the government, universities and industries, which are involved in human capital development and workforce employment in any country. The idea of having collaboration among all these partners in information system is really vital, as in isolation those three big icons cannot produce optimum output for a country. The prime objective of this study is to investigate the possibility of collaborating the Government, University and Industry (GUI) at a standard online platform where each of them is able to access, exchange, and represent information for the greater benefit of the citizens for a particular country, especially in the context of Malaysia. The description of the partners includes the functionalities and information services offered by each of the collaborative icon together with brief concept of implementation mechanism. As the expected outcome, the citizens would get ample information based on their needs. The discussion incorporates the justification of why three partners have been chosen for collaboration in this study. Finally, future implications indicate the direction of the design and successful implementation of this study.